Five-Level Inverter-Fed Space Vector Based Direct Torque Control of Open-End Winding Induction Motor Drive - Vinod, B. R.; Baiju, M. R.; Shiny, G. (IEEE transactions on energy conversion, 2018)
This work proposes a space vector based direct torque control scheme implemented on an open-end winding type induction motor fed by a five-level inverter. The modulation algorithm uses a 60-degree coordinate system to avoid fractional arithmetic as present in the standard Cartesian coordinate system, which reduces the arithmetic calculation complexity. Making use of the natural fractal structure of a hexagonal space vector diagram of the multilevel inverter, this scheme uses a fractal-based algorithm for sector identification and switching vector generation. In this scheme, three-phase signals to the space vector modulator are generated based on a torque-flux error by means of transformation logic. Two three-level inverters are fed from both open ends of an induction motor for realizing a five-level inverter. The scheme includes implementation of different levels of inverter-fed direct torque control drive. The control scheme is implemented on a laboratory prototype 2hp induction motor through a TMS320F240 DSP processor based dSPACE DS-1104 controller. The inverter gating signals are generated by using a Virtex-II FPGA board. The hardware results of different direct torque control configurations are presented for validating the algorithm and all the measurements are done under closed-loop operation.